2003
DOI: 10.1046/j.1095-8649.2003.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural hybridization between endangered and introduced species of Pseudorasbora, with their genetic relationships and characteristics inferred from allozyme analyses

Abstract: From 25 populations of Pseudorasbora in Japan, polymorphism at 22 allozyme loci indicated that the level of genetic differentiation between Pseudorasbora parva and Pseudorasbora pumila (D = 0·421–0·517) was greater than that between the two subspecies of P. pumila, P. pumila pumila and P. pumila subsp. (D = 0·164), consistent with morphological differences. While P. parva displayed genetic variation (H = 0·003–0·100) similar to other freshwater fishes, P. pumila pumila and P. pumila subsp. populations showed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 18 publications
1
31
0
1
Order By: Relevance
“…Pseudorasbora pumila (Japanese name, shinai-motsugo), an endangered species of freshwater minnow in Japan, has largely been replaced by the accidentally introduced species, Pseudorasbora parva (Japanese name, motsugo) as a result of intensive hybridization (Uchiyama, 1987;Konishi et al, 2003). The frequent natural hybridization between P. pumila and P. parva is direct evidence that the two species share mating behaviors and compete for reproductive resources.…”
Section: Methodsmentioning
confidence: 98%
“…Pseudorasbora pumila (Japanese name, shinai-motsugo), an endangered species of freshwater minnow in Japan, has largely been replaced by the accidentally introduced species, Pseudorasbora parva (Japanese name, motsugo) as a result of intensive hybridization (Uchiyama, 1987;Konishi et al, 2003). The frequent natural hybridization between P. pumila and P. parva is direct evidence that the two species share mating behaviors and compete for reproductive resources.…”
Section: Methodsmentioning
confidence: 98%
“…Hosoya and Maehata (1994) inferred that one of the causes for displacement by P. parva might have been hybridization between the species, because of overlapping of breeding seasons of the two species (Nakamura, 1969) and the easy occurrence of both natural and artificial hybridization (Hosoya and Maehata, 1994;Kasama et al, 1990). Recently, Konishi et al (2003) found that in Nagano Prefecture (Honshu), the two species have hybridized easily under natural conditions, but cannot coexist in the long term, P. pumila pumila being displaced by P. parva.…”
mentioning
confidence: 99%
“…in Japan (Matsubara, 1982;Sato, 1982;Kawamura et al, 2001;Konishi et al, 2003). To make clear these biological phenomena, ecological and genetic studies are indispensable for the sympatric populations comprising closely related native and nonnative fish species.…”
mentioning
confidence: 99%
“…Allozyme polymorphisms have commonly been used for phylogenetic inferences in various fish species (Exadactylos and Thorpe, 2001;Cammarata et al, 2002;Konishi et al, 2003;Swartz et al, 2004;Turan et al, 2005). In the present study the pattern of phylogenetic relationships of two genera, including four species, M. barbatus, M. surmuletus, U. moluccensis, U. pori, and one subspecies, M. b. ponticus, living in the Mediterranean Sea, were investigated together with genetic and morphological characters.…”
Section: Introductionmentioning
confidence: 99%